EFEKTIFITAS APLIKASI CAKE TERHADAP KEMAMPUAN PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA - Agus Wilson; Sutrisno Sutrisno (Universitas Indraprasta PGRI, 2022)
This research is based on the low ability of English vocabulary mastery of accounting and finance students class X, SMK PGRI Tambun Bekasi. This research is aimed as follows: To analyze the effect of Cake learning applications uses towards students' English vocabulary mastery. The method in this research is Regression Analysis that used to find the effect of Cake learning application uses on students' English vocabulary mastery. This research is expected to be another alternative solution for the teachers when choosing an effective application media to be used in enhancing students' English vocabulary mastery. Based on the results, it can be concluded that the Cake learning application can be used to improve students’ vocabulary mastery. The result of the study identifies that is effects of using Cake applications towards students' English vocabulary mastery. It can be proven that there is a significant effect of using Cake learning media on students' English learning outcomes (sig. = 0.006 < 0.05 and F count = 7.842). There is a significant effect of student interest in learning English (sig. = 0.026 < 0.05 and F count = 5.134). There is a significant interactive effect of learning media and students' interest in learning English (sig. = 0.018 < 0.05 and F count = 5.824)